MEANS OF IMAGE CREATION OF RUSSIAN MILITARY MEN IN ENGLISH TEXTS ABOUT THE CRIMEAN WAR (1853-1856): LINGUOIMAGOLOGICAL ASPECT - Andriy A. Moroz (Alfred Nobel University Journal of Philology)
This study explores the linguistic representation of Russian national and military identity in 19th-cen- tury English-language narratives, with a focus on the Crimean War (1853-1856). Grounded in linguoimagol- ogy – an interdisciplinary approach that analyzes how national images are formed and transmitted through language – this research off ers a comparati ve literary-linguisti c perspecti ve on how English authors verbal- – this research off ers a comparati ve literary-linguisti c perspecti ve on how English authors verbal- – this research off ers a comparati ve literary-linguisti c perspecti ve on how English authors verbal- this research off ers a comparati ve literary-linguisti c perspecti ve on how English authors verbal- this research offers a comparative literary-linguistic perspective on how English authors verbal- ized their image of Russians during this pivotal historical period. The primary aim of the article is to identify and interpret the linguistic means used by English authors to construct the image of Russians during the Crimean War. This issue remains largely unexplored in both domestic and international linguistics. To achieve this aim, the following objectives were addressed: to an- alyze English-language depictions of the Russian military under Nicholas I and Alexander II; to identify pos- itive and negative evaluations of Russian identity using linguoimagologemes such as: topographic and an- thropological images of Russian proper names as seen by the British; Russians’ love of state awards as Seen by the British; piousness of Russians as Seen by the British; to determine the specific linguistic devices em- ployed by British authors to assess and portray the Russian army and national character. The study applies synchronous linguoimagological analysis using specialized terms such as macro- linguoimagotheme, linguoimagotheme, linguoimageme, and linguoimagologeme. This methodological framework enables the identification of national images through a detailed examination of textual fea- tures across historical, journalistic, and autobiographical English narratives from the mid-19th century. Key Linguistic Devices Identified: lexical tools [use of evaluative adjectives (e.g., “insignificant,” “de- cayed”) and emotionally loaded epithets (e.g., “fanaticism,” “ostentatious”); semantic fields involving mil- itary valor, religious fervor, and political symbolism; metaphorical framing to convey irony or exaggera- tion (e.g., “a wave of superstition”)]; syntactic tools (impersonal constructions and passive voice that ob- scure agency (e.g., “it was said that…”); complex sentence structures with embedded commentary (e.g., “Although the officer appeared dignified, his medals seemed exaggerated”); use of metadiscourse markers (e.g., “of course,” “as expected”) to frame reader interpretation); stylistic tools (strategic irony and juxta- position (e.g., sacred ritual vs. personal piety); tone modulation ranging from respect to sarcasm; onomas- tic transformations such as “Menchikoff” for “Menshikov” to reflect rhetorical distancing); narrative strate- gies (authorial detachment and implied superiority; cultural distancing through frequent references to Rus- sian “otherness”; construction of national identity via contrastive framing with British norms). This research demonstrates that English-language portrayals of Russians during the Crimean War were shaped by a combination of cultural bias, ideological framing, and linguistic devices. Russian prop- er names were systematically distorted, indicating both phonetic adaptation and rhetorical alienation. The visibility of medals and ceremonial symbols was exaggerated through visual hyperbole, reflecting British views on Russian state symbolism. Religious depictions fluctuated between collective fanaticism and indi- vidual sincerity, revealing a dual-layered construction of Russian piety. The study contributes a novel linguoimagological model for analyzing how nations are constructed through language. It underscores how lexical, syntactic, and stylistic mechanisms interact to reinforce na- tional stereotypes and oppositional cultural narratives. These findings are relevant to fields such as histor- ical discourse analysis, linguocultural studies, and intercultural communication and may serve as a founda- tion for further studies of national images in literary or historical contexts.